Effect of immunosuppressive agents on the blastogenic response of mouse spleen T and B lymphocytes. I. Culture conditions and the evaluation system - Pospísil, M; Dráber, P; Hofman, J; Nouza, K; Klapácová, J (Folia biologica, 1978)
A microplate culture system has been standardized for blastic transformation of lymphocytes, using various mitogens more or less specific to T lymphocytes (concanavalin A, phytohaemagglutinin, erythrogenic toxin) or B lymphocytes (lipopolysaccharides and their lipids A, pokeweed mitogen). The mitogen-stimulated lymphocyte activation was examined by the use of the nucleolar test determining the state of nucleolar RNA synthesis by morphologic criteria. In this introductory paper to a series of papers analyzing the specificity of action of the various chemical and biological immunosuppressive agents on the blastogenic responses of T and B lymphocytes, optimal concentrations of cells and blastogenic substances and other parameters were tested, and the kinetics of transformation was investigated in detail.
Keywords: kultivované buňky; buněčné jádro; T-Lymphocytes; Lymphocytes; Lipopolysaccharides; T-lymfocyty; lymfocyty; Mice; kostní dřeň; slezina; metody; Cells, Cultured; B-lymfocyty; aktivace lymfocytů; Cell Nucleus; Methods; lektiny; zvířata; B-Lymphocytes; Lectins; Lymphocyte Activation; lipopolysacharidy; Thymus Gland; myši; Bone Marrow; thymus; Spleen; Animals